2019
DOI: 10.1002/pra2.114
|View full text |Cite
|
Sign up to set email alerts
|

Examination of online information search stopping behaviors and stopping rules by task type

Abstract: This poster aims to understand how task type could influence when people would stop searching and what stopping rules people would use in the following three stopping behaviors: query stopping, read stopping, and task stopping during online information search. We conducted a pilot user experiment with four participants; each performed two different types of search tasks. The results show two different patterns of stopping behavior on well‐structured and decomposable tasks and poorly structured and indecomposab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…While the authors did an excellent job of defining the scope of IE and its interruptions, studies of searchers' stopping behaviors during active information seeking (e.g., Wu & Kelly, 2014;Maxwell et al, 2015;Dedema & Liu, 2019) are also pertinent. For example, Maxwell et al (2015) found that searchers most often stopped their review of results after seeing too many non-relevant results, i.e., when they'd reached the point of frustration.…”
Section: Commentarymentioning
confidence: 99%
“…While the authors did an excellent job of defining the scope of IE and its interruptions, studies of searchers' stopping behaviors during active information seeking (e.g., Wu & Kelly, 2014;Maxwell et al, 2015;Dedema & Liu, 2019) are also pertinent. For example, Maxwell et al (2015) found that searchers most often stopped their review of results after seeing too many non-relevant results, i.e., when they'd reached the point of frustration.…”
Section: Commentarymentioning
confidence: 99%